2010
DOI: 10.1007/s10803-010-0958-2
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Psychiatric Disorders Associated with Asperger Syndrome/High-functioning Autism: A Community- and Clinic-based Study

Abstract: The present study identifies the prevalence and types of comorbid psychiatric disorders associated with Asperger syndrome (AS)/high-functioning autism (HFA) in a combined community- and clinic-based sample of fifty 9- to 16-year-old subjects using the Schedule for Affective Disorders and Schizophrenia for School-Age Children, Present and Lifetime Version. The level of functioning was estimated using the Children's Global Assessment Scale. The results support common (prevalence 74%) and often multiple comorbid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
213
6
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(241 citation statements)
references
References 53 publications
18
213
6
4
Order By: Relevance
“…Furthermore, up to 24% of young people with ASD experience depressive symptoms (Leyfer et al 2006). While depression does not co-occur as frequently as anxiety in young people with ASD, its prevalence is higher than in the general population and can be highly functionally impairing (Kim et al 2000;Mattila et al 2010). Since alexithymia occurs more frequently in individuals with ASD, it may be related to the elevated emotional difficulties also observed in this group.…”
Section: Alexithymia and Internalising Disordersmentioning
confidence: 99%
“…Furthermore, up to 24% of young people with ASD experience depressive symptoms (Leyfer et al 2006). While depression does not co-occur as frequently as anxiety in young people with ASD, its prevalence is higher than in the general population and can be highly functionally impairing (Kim et al 2000;Mattila et al 2010). Since alexithymia occurs more frequently in individuals with ASD, it may be related to the elevated emotional difficulties also observed in this group.…”
Section: Alexithymia and Internalising Disordersmentioning
confidence: 99%
“…In samples of children with ASD, studies have found that the children scored within the clinical range for least one other comorbid psychiatric disorder for up to 95% [27,28] in a sample that had been referred for treatment [29]. More specifically, many children with ASD meet the criteria for disruptive behavior disorders [e.g., attention-deficit/hyperactivity disorder (ADHD), oppositional defiant disorder (ODD)], anxiety, or affective disorders [30,31]. Recent studies with adults with ASD suggest that many of these comorbidities continue or develop in adulthood as well [32][33][34] prompting more interest in how best to assess and treat potential comorbid pathologies, discriminant from ASD symptoms, in clinical practice [35].…”
Section: Comorbid Psychopathologymentioning
confidence: 99%
“…ADHD, mood disorders, and anxiety are described in the population, and the overall rate of comorbid psychiatric conditions has been estimated to be as high as 74%. 11,12 The case by Jennifer F. Le, MD (see page 414) illustrates the decision process necessary when patients with ASD require pharmacologic management. The case illustrates guidelines for the clinician, as medication should not be the only modality of treatment involved and should be directed at targeted symptoms and not core symptoms of autism.…”
Section: Pediatrician's Role In Asd Treatmentmentioning
confidence: 99%